(untitled) (Journal of actual problems of jurisprudence, 2016)
This article is dedicated to the questions of legal regulation of realization of the right of persons and corporations to the equivalent compensation for coercive alienation of their land plots. Particularly, the attention was given to the judicial features and order. Moreover, the list of expenses allowed to be included to the price is defined.